PHENOTYPIC, GENETIC AND ENVIRONMENT CORRELATION BETWEEN TRAITS OF HYBRID MAIZE - NARDINO, Maicon (2016)
Maize is one of the three major cereals produced in the world, taking an increasing demand on its production, generates challenges to maize breeders. Phenotypic, genetic and environment correlations constitute an important tool to aid the breeder in the indirect selection of traits. This work had as objective to analyze the phenotypic (rP), genetic (rG) and environment (rE) correlations, as well as estimate the correlated response and the contribution of genetic and non-genetic effects on phenotypic correlation between characters of agronomic importance in hybrid maize, cultivated on different locations. The work was conducted in the cities of Guaraciaba-SC, Palmas-PR, Ampére-PR and Clevelãndia-PR and 27 single hybrids were used, developed by KSP seeds Ltda. The following agronomic characters were evaluated: car diameter, ear weight, ear grain weight, cob diameter, cob weight, prolificity, yield and weight of a thousand grains. There was a predominance of non genetic effects on phenotypic correlation for some pairs. Direct selection to increase the diameter of the ear and ear mass indirectly increases the mass of grains grains and thousand grain weight. The direct selection for increased row by grain number provides indirect gains on the number of grains ear.